Financing the Reconstruction of Public Capital after a Natural Disaster - Bevan, David (World Bank, Washington, DC, 2016)
When a natural disaster destroys public capital, these direct losses are exacerbated by indirect losses arising from reduced output while reconstruction takes place. These indirect losses may be much larger, relative to the direct ones, in low-income countries, because they lack the finance for rapid reconstruction. This paper uses a dynamic general equilibrium model to examine sovereign disaster risk insurance, increased taxation, and budget reallocation as alternative financing mechanisms for countries where increased borrowing is impractical. The analysis suggests that insurance may or may not be helpful, depending on detailed circumstances, and that budget reallocation is potentially very damaging. Raised taxation, if feasible, may be an attractive option.